Avaliação do nível sérico de interleucina-3 como marcador prognóstico na sepse - Isabela Nascimento Borges (2016)
A recent study has shown that interleukin 3 (IL-3) plays a key role in the pathophysiology of sepsis and septic shock, and that high levels of this cytokine predict poor prognosis. The aim of this study was to evaluate the IL-3 prognostic role in patients with sepsis in an intensive care unit, considering hospital mortality as the primary outcome. An ambispective cohort was conducted in the Intensive Care Unit of the Hospital das Clinicas, Universidade Federal de Minas Gerais. Adult patients with sepsis or septic shock initiated within 48 hours were included and followed until hospital discharge or death. IL-3 levels on days 1, 3 and 7 from inclusion were measured in serum and associated with clinical and laboratory variables. Additionally we assessed the levels of pro and anti-inflammatory cytokines (profiles Th1, Th2 and Th17) at inclusion. One hundred and twenty patients were included from October / 2012 to January / 2016, twenty (17%) with sepsis and one hundred (83%) with septic shock. The average age of the population was 55 (± 18) years and 68 (57%) patients were male. The median APACHE II and SOFA scores at inclusion were 17 (Q1-Q3: 12-22) and 8 (Q1-Q3: 6-11) points, respectively. The mortality observed after 28 days, in the ICU, and in the hospital was 24%, 22.5% and 34%, respectively. Serum levels of IL-3 measured at inclusion were significantly higher among patients who died compared with patients who survived at hospital discharge (91.2 pg / ml vs 36.0 pg / ml, p = 0.024). Initial values of IL-3 above 127.5 pg / ml were significantly associated with hospital mortality (p = 0.019; OR = 2.97, 95% CI 1.27 to 6.97). This association remained present in a multivariate analysis (p = 0.01) adjusted for APACHE II and PCR. In Cox survival model considering IL-3 levels measured at inclusion, patient's age and sequential values of SOFA, IL-3 values remained independent associated with mortality (p = 0.005). The levels of IL-6 and IL-10 measured on day 1 were also significantly higher in those who died in hospital. In conclusion, serum IL-3 levels of septic patients measured from the time of admission in intensive care correlates with prognosis. Higher levels of this cytokine were shown to be independently associated with hospital mortality in this population, even after adjusting for age, APACHE II and SOFA.